Răspuns :
a=b+873
a:b=12 rest 15 => a=12b+15
b+873=12b+15
11b=858
b=78
a=78+873
a=951
5b=3c
5x78=3c
390=3c
c=390:3
c=130
a+b+c=78+951+130=1159
din a:b=12 (rest 15) rezulta ca a = 12b+15
↓
12b+15 - b = 873 → 11b = 873 - 15 = 858
b = 78 √
→ a = 12*78+15 = 951 √
din 5b=3c → 5*78 = 3 c adica: c = 78*5 : 3 =26*5 = 130 √
⇒ a + b + c = 951+78+130 = 1159 √√
↓
12b+15 - b = 873 → 11b = 873 - 15 = 858
b = 78 √
→ a = 12*78+15 = 951 √
din 5b=3c → 5*78 = 3 c adica: c = 78*5 : 3 =26*5 = 130 √
⇒ a + b + c = 951+78+130 = 1159 √√